The Q theory and the Swedish housing market - an empirical test - Lennart Berg; Tommy Berger (Uppsala University, Department of Economics, 2005)
We argue that major changes in economic policy have resulted in a more market driven demand for housing investment in Sweden as a result of changes in policy during the end of the 1980s and beginning of the 1990s. The used investment theory is Tobins transparent Q theory. Our results indicate, for the last period of the sample (1993-2003 quarterly data) that a high degree of correlation between the Q ratio and the (logarithm of) two different variables for housing investment exist. An error correction regression model, controlling for structural breaks, indicates also a stable long run relationship could be detected for the logarithm of building starts and the Q ratio between 1993-2003 but not between 1981-1992.
urn:nbn:se:uu:diva-74358
Keywords: E22; R21; 330; Tobin's Q; housing investment; error correction model; structural break; Tobin's Q; Immobilienwirtschaft; Schätzung; Schweden; Fehlerkorrekturmodell